Integrated marketing communication – towards a holistic concept - Daszkiewicz, Magdalena; Pukas, Anetta (Management Sciences, 2016)
This paper explores the concept of Integrated Marketing Communication (IMC) and presents changes resulting from its evolution. The purpose of this paper is to determine directions of development of the IMC concept and facilitate future research and empirical implementation of integrated marketing communication. Based on a descriptive review of the scientific literature, relevant and significant to the marketing communication knowledge, the authors established the state of development of the IMC concept. The overview of prevailing theories enabled the comparison of the existing definitions and main features of the concept. The paper presents changes and key drivers for the evolution of IMC. The analysis allowed the authors to identify new approaches to the concept of IMC in the world science and determine that the modern IMC concept is moving toward holistic solutions, which include strategic planning in the organisation and modern marketing knowledge. Nowadays, the integration of marketing communications means the need to seek solutions at a strategic level and value creation based on long-term relationships with customers. The future of the IMC concept also means the need to conduct studies that will determine the possibility of its use in relation to different types of organisations (non-profit organisations or administrative units etc.), as well as various industries or business sectors
Nauki o Zarządzaniu = Management Sciences, 2016, Nr 3 (28), s. 20-29
Keywords: marketing communication; integrated marketing communication; komunikacja marketingowa; zintegrowana komunikacja marketingowa